Enmarcando Attica: construcción mediática de la prensa acerca de la rebelión en la prisión de Attica: los reclamantes, la prominencia del marco y la geografía cultural de los lectores (2017)
Using frame analysis, the authors examine how historical narratives of the 1971 Attica Prison riot were driven in part by frame diversity and salience across differing cultural geographies. Comparison of constructed meaning in news articles published by the New York Times, the Chicago Tribune, and the Chicago Defender is presented. Viewpoints regarding the prison riot are linked to claims-makers sourced by the differing news outlets and contextual differences in portrayal are discussed with regard to the media's role in socially constructing perceptions of the Attica riot. Included is discussion regarding public policy agenda setting, triggering events, and the capacity of news media to shape local ways of knowing. Methodological considerations are presented linking media analysis, claims-making research, and cultura criminology theory to current forms of media presentation and future qualitative approaches to media analysis.